Method performance study of on-line internal standard addition in inductively coupled plasma mass spectrometry - András Törvényi (2018)
The approach of adding an internal standard to all solutions at a constant level, by on-line merging of the internal standard (steady state) and the sample solution streams, was studied for multi element determinations using inductively coupled plasma mass spectrometry. An internal standard introduction system was developed using a knotted reactor, a mixing T-piece and two peristaltic pump channels. The tube length of the knotted reactor and the wash out time were optimized for achieving the best mixing efficiency. The performance of the optimized system was compared to the traditional method of internal standard addition (batch) and checked by analysis of the NIST 8415 SRM (egg powder). The uncertainty components of the internal standard addition were also evaluated and its contribution to the combined measurement uncertainty estimated. No significant difference was found in terms of accuracy and precision between the two methods. However, the new technique was proved to be very practical, robust and less time consuming than the traditional approach. © The Royal Society of Chemistry 2007.